Soviet View of the World. Exploring Long-Term Visual Patterns in “Novosti dnia” Newsreel Journal (1945-1992) - Mila Oiva; Tillmann Ohm; Ksenia Mukhina; Mar Canet Solà; Maximilian Schich (Journal of Cultural Analytics)
Newsreels, short documentary news films, were an influential channel of mass communication and propaganda in the Soviet Union. They served as an important means of visualizing the world for audiences in the way the Soviet authorities wanted it to be depicted. Studies in Soviet visual culture have recognized both continuities of repeating patterns and changes in the post-World War II period. This understanding is based primarily on temporally limited source selections, while a more systematic study of the developments in Soviet visual culture over a longer period is pending. In this article, we reveal long-term continuities, subtle changes, and sudden shifts in the official visual discourse in the Soviet newsreel series ‘Novosti dnia’ (News of the Day) 1945 to 1992. We study visual patterns in approximately 1,700 digitized newsreel issues, each about ten minutes long, using multidimensional vector embeddings. These embeddings, produced from the central frames of 205,678 shots, help visually evaluate the footage and assess visual similarities based on ResNet50 feature vectors. For this, we use the _Collection Space Navigator_ tool. The article demonstrates how multidimensional vector embeddings can be used to study the internal time of the films, and the external time of the years running by.